A tale of rights and wrongs: Stories and storytelling on the issue of asylum seeker boat arrivals to Australia - Hansford, Mai (2017)
This thesis examines stories and storytelling about asylum seeker boat arrivals to Australia in 2009-2011. It aims to answer the questions ‘Who gets to be heard?’ and ‘What stories are told?’ on this issue. Research is undertaken in three different sites and focuses on two key incidents.The first site is with members of an activist public (in interviews) advocating for change to Australia’s treatment of asylum seekers. The second site is practices and newspaper articles of journalists in the media industry. The final site is in a space in-between, a site where the activists produce media releases to offer the group’s stories for inclusion in media portrayals. The logic that underpins the examination of the stories in the three sites in this study is the marriage of Symbolic Convergence Theory (SCT) (Bormann 1982) – to understand the stories and storytelling processes – with theories from public relations, social movements and media studies specific to individual sites. In addition, theories of power and hegemony are deployed to examine the relationships among the stories collected from the different sites. The key finding identifies a national story that dominates in the newspaper articles. However, the thesis also discerns three key alternative stories that emerge from the activists’ individual and public relations storytelling. Framing both the dominant national and the alternative stories are histories of racism, Australian nationalism and facticity. Despite marked differences in the stories in the three sites their underlying drivers are similar. The thesis illustrates the common yet different uses of themes of history, righteousness and connectedness